Answers

The Brainliest Answer!
2016-05-01T06:05:15+05:30
Solutions 

 \left \{ {{y=5x-8} \atop {x=6x+3}} \right.  

Arrange equation  variables for elimination :

 \left \{ {{y-5x=-8} \atop {x-6x=3}} \right.
   y -   6x = 3
-  y -  5x = -8
______________
-x =  11

For y :

y - 6 x = 3

y - 6 ( - 11 ) = 3

y + 66 = 3

y = 3 - 66

y = -63

x = - 11      y = -63
1 5 1
2016-05-01T09:52:31+05:30
5x-y=8---------------1
6x-y=3---------------2
multiply  i by 6 and ii by 5,we get
30x-6y=48
30x-5y=15
0-11y=33
y=3
putting y=3 in ii ,we get
6x-3=3
6x=6
x=1
0